Antiarrhythmic Action of Flecainide in Polymorphic Ventricular Arrhythmias Caused by a Gain‐of‐Function Mutation in the Nav1.5 Sodium Channel. Issue 4 (7th October 2015) - Amarouch, Mohamed Y.; Swan, Heikki; Leinonen, Jaakko; Marjamaa, Annukka; Lahtinen, Annukka M.; Kontula, Kimmo; Toivonen, Lauri; Widen, Elisabeth; Abriel, Hugues
Abstract : Background: The cardiac sodium channel Nav 1.5, encoded by the gene SCN5A, is associated with a wide spectrum of hereditary arrhythmias. The gain‐of‐function mutation p.I141V in SCN5A was identified in a large multigenerational family with exercise‐induced polymorphic ventricular arrhythmias. The purpose of this study was to evaluate the molecular and clinical effects of flecainide administration on patients with this syndrome. Methods: Eleven p.I141V carriers who exhibited frequent multiformic premature ventricular complexes (PVCs) during exercise were subjected to exercise stress tests, both before and after intravenous infusion of 2 mg/kg flecainide. The in vitro effects of flecainide were evaluated using the patch‐clamp technique with HEK293 cells expressing the Nav 1.5 channel. Results: The flecainide treatment significantly reduced the frequency of PVCs during and after exercise. Next, the sensitivity of the p.I141V mutant channel to flecainide was compared to that of the wild type channel. Perfusion of flecainide inhibited the peak and window currents in both groups. Conclusion: The clinical investigations of the affected patients, as well as the molecular and pharmacological characterization of the SCN5A p.I141V mutation, provide new evidence supporting the association of this mutation with exercise‐induced polymorphic ventricular arrhythmias. These data also demonstrate that flecainide may serve as an effective treatment for the defect in Nav 1.5 that leads to an increased sodium window current.